Application of in-vitro micropropagation technique for sustainable production of four local taro cultivars [Colocasia esculenta (L.) Schott] in Cameroon - Manju, B.E.; Mbong, A.G.; Fokunang, Charles N.; Tembe-Fokunang, E.A.; Hanna, R. (Academic Journals, 2017)
Taro leaf blight disease has recently been reported in Cameroon to cause between 50 and 100% yields loss of taro in most of the agro-ecological crop growing regions. This has led to a significant reduction in disease-free planting materials, edible crop and increased. The Meristem culture technique has been used to produce crop plants free of viruses and fungi especially in vegetative propagated colocassia plants. This aimed at applying in-vitro micro-propagation technique for sustainable production of four local taro cultivars in Cameroon. This study was conducted at the Root and Tuber Tissue Culture Laboratory, of the Institute of Agricultural Research for Development (IRAD), Bambui from April 2015 to November 2016. Micro-plants from four local taro cultivars were produced in vitro from apical meristem tips. The tip meristems were excised from corms of the four local taro cultivars. The excised explants were surface sterilized with alcohol and sodium hypochlorite in sequence steps at different concentrations. Meristems were cultured at establishment stage on Murashige and Skoog (MS) medium with 30 g of sugar, 1.1 ml of 6-benzylaminopurine and 7 g of agar. Shoots proliferation was induced in MS with 2.2 ml of 6-benzylaminopurine (BAP). Result shows a significant difference at p≤0.5 in number of shoots, petiole length, open leaf and corm diameter among the cultivars and no significant variation in mean number of senescence leaf with respect to all the cultivars, at 60 days of shoot tip culture. At rooting stage, taro shoots were cultured on MS media supplemented with 10 ml of 0.1 mg/ml naphthalene acetic-acid (NAA). Roots were produced on all the cultivars with excellent mean growth rate of 14.7 ± 0.69 recorded in cultivar with dark green petiole and small leaves.